The correlation matrix of random solutions of a dynamical system with Markov coefficients - Lapshin, A. L. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
For dynamical systems which are described by systems of differential or difference equations dependent on a finite-valued Markov process, we suggest a new form of equations for moments of their random solution. We derive equations for a correlation matrix of random solutions.